The Influence of Product Quality, Payment Methods, and Timeliness of Delivery at Marketplace Shopee on Purchase Decisions (Survey on Students of Muhammadiyah Palu University) - Cahyaning Raheni; Umar; Farid; Nasrulhak Akkas; Annas Hidayat Dj Sipanabi (Jurnal Sinar Manajemen, 2024)
The purpose of this study was to determine whether product quality, payment methods, and timely delivery on the Shopee marketplace partially and simultaneously influence purchasing decisions. The approach used in this study is a quantitative type using an associative survey method and using multiple regression analysis, and for the sampling technique using probability sampling technique. The research results obtained in this study are product quality on the Shopee marketplace which has a partial effect on purchasing decisions, this is evidenced by the results of tcount 4.332 > ttable 1.986 and a significant value of 0.000. The payment method on the Shopee marketplace has a partial effect on purchasing decisions, this is proven by the results of tcount 4,824 > ttable 1,986 and a significant value of 0.000. Timeliness of delivery on the Shopee marketplace has a partial effect on purchasing decisions, this is proven by the results of tcount 6,299 > ttable 1,986 and a significant value of 0.000. Meanwhile, based on the results of simultaneous test statistical calculations, it can be concluded that Product Quality, Payment Methods, and Timeliness of Delivery on the Shopee marketplace simultaneously influence purchasing decisions, this is proven by the test results fcount 98,854 > ftable 2.70 and a significance value of 0.000, as well as a coefficient of determination of 0.765 which is percentaged to 76.5%, which means that purchasing decisions can be explained by product quality, payment methods and timely delivery with quite a high rate and for the rest explained by other variables.